2019
DOI: 10.1177/1350650119852568
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of magnetohydrodynamic partial slip laser bump texture slider and journal bearing

Abstract: A model of magnetohydrodynamic partial slip laser texture bearing (slider and journal) is developed. The influence of laser bump texture and slip laser texture partial configuration on the magnetohydrodynamic performance analysis of bearing is presented. An electrically conducting fluid is confined to bearing surfaces under uniform magnetic field perpendicular to slider bearing and inclined to the line of maximum film thickness to journal bearing. A one-dimensional analysis based on the narrow groove theory is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
7
0
1
Order By: Relevance
“…The supports at the two radial bearings are elastic supports that meet the actual situation. The calculation of bearing stiffness and damping coefficient adopt narrow bearing theory and Gampbell boundary conditions [24,25].…”
Section: Boundary Conditionmentioning
confidence: 99%
“…The supports at the two radial bearings are elastic supports that meet the actual situation. The calculation of bearing stiffness and damping coefficient adopt narrow bearing theory and Gampbell boundary conditions [24,25].…”
Section: Boundary Conditionmentioning
confidence: 99%
“…(Yamasaki and Shioda, 1977;Rosa et al, 1991;Jang and Lee, 2000). MHD bearings significantly rises load-carrying capacity comparing to conventional bearings (Maki et al, 1966;Fathima et al, 2015;Naduvinamani et al, 2017;Rao et al, 2019;Mouda et al, 2019;Hanumagowda et al, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…Later, Susilowati et al [21] revealed that the combined techniques of texture and slip have a significant influence on the enhancement of the tribological performance of a bearing. Subsequently, Rao et al [15,[22][23][24] have investigated the beneficial effects and potential of partial slip-texture on the enhancement of the load support, the friction coefficient and the stability of the bearing, either Newtonian or Non-Newtonian lubricated. The same authors also showed that heterogeneous slip/no-slip pattern is superior to textured-slip pattern in terms of the load support and friction coefficient in the case of micro-polar and power-law fluid lubricated journal bearings [22] and the case of magnetohydrodynamic lubrication [24].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Rao et al [15,[22][23][24] have investigated the beneficial effects and potential of partial slip-texture on the enhancement of the load support, the friction coefficient and the stability of the bearing, either Newtonian or Non-Newtonian lubricated. The same authors also showed that heterogeneous slip/no-slip pattern is superior to textured-slip pattern in terms of the load support and friction coefficient in the case of micro-polar and power-law fluid lubricated journal bearings [22] and the case of magnetohydrodynamic lubrication [24]. In these studies, however, the non-mass conserving cavitation algorithm has been employed and the results were questionable, as first investigated by Ausas et al [25].…”
Section: Introductionmentioning
confidence: 99%